The Dengue Outbreak of 2023: A Wake-Up Call for Healthcare Professionals and Policymakers for Effective Prevention and Control Strategies - Islam, Quazi Tarikul (Journal of Medicine, 2024)
Abstract not available J MEDICINE 2024; 25: 1-3